Immunotherapy in Parkinson’s Disease: Micromanaging Alpha-Synuclein Aggregation - George, Sonia (J Parkinsons Dis, 2015)
Currently, several α-synuclein immunotherapies are being tested in experimental Parkinson’s disease models and in clinical trials. Recent research has revealed that α-synuclein is not just an intracellular synaptic protein but also exists extracellularly. Moreover, the transfer of misfolded α-synuclein between cells might be a crucial step in the process leading to a progressive increase in deposition of α-synuclein aggregates throughout the Parkinson’s disease brain. The revelation that α-synuclein is present outside cells has increased the interest in antibody-based therapies and opens up for the notion that microglia might play a key role in retarding Parkinson’s disease progression. The objectives of this review are to describe and contrast the use of active and passive immunotherapy in treating α-synucleinopathies and highlight the likely important role of microglia in clearing misfolded α-synuclein from the extracellular space.